Intrauterine nutrition: long-term consequences for vascular health - Szostak-Wegierek D (International Journal of Women's Health, 2014)
Dorota Szostak-WegierekDepartment of Human Nutrition, Medical University of Warsaw, Warsaw, Poland Abstract: There is a growing body of evidence that improper intrauterine nutrition may negatively influence vascular health in later life. Maternal malnutrition may result in intrauterine growth retardation and, in turn, metabolic disorders such as insulin resistance, diabetes, hypertension, and dyslipidemia, and also enhanced risk of atherosclerosis and cardiovascular death in the offspring. Energy and/or protein restriction is the most critical determinant for fetal programming. However, it has also been proposed that intrauterine n-3 fatty acid deficiency may be linked to later higher blood pressure levels and reduced insulin sensitivity. Moreover, it has been shown that inadequate supply of micronutrients such as folate, vitamin B12, vitamin A, iron, magnesium, zinc, and calcium may contribute to impaired vascular health in the progeny. In addition, hypertensive disorders of pregnancy that are linked to impaired placental blood flow and suboptimal fetal nutrition may also contribute to intrauterine growth retardation and aggravated cardiovascular risk in the offspring. On the other hand, maternal overnutrition, which often contributes to obesity and/or diabetes, may result in macrosomia and enhanced cardiometabolic risk in the offspring. Progeny of obese and/or diabetic mothers are relatively more prone to develop obesity, insulin resistance, diabetes, and hypertension. It was demonstrated that they may have permanently enhanced appetites. Their atheromatous lesions are usually more pronounced. It seems that, particularly, a maternal high-fat/junk food diet may be detrimental for vascular health in the offspring. Fetal exposure to excessive levels of saturated fatty and/or n-6 fatty acids, sucrose, fructose and salt, as well as a maternal high glycemic index diet, may also contribute to later enhanced cardiometabolic risk. Keywords: maternal malnutrition, intrauterine growth retardation, maternal overnutrition, macrosomia, adult cardiovascular disease